2016
DOI: 10.1177/0739986316671297
|View full text |Cite
|
Sign up to set email alerts
|

Familism Is Associated With Psychological Well-Being and Physical Health

Abstract: Familism is a core Latino value that emphasizes close family relationships and prioritizing of family before the self. Familism has implications for well-being and health, but it is not clear whether these values are generally beneficial or beneficial under stress. We examined whether the associations of familism with well-being/health were consistent with a main effect or stress-buffering model in Latinos and non-Latinos. Latino (n = 171), European (n = 225), and East Asian Americans (n = 415) completed measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
67
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 34 publications
4
67
1
1
Order By: Relevance
“…While most research has focused on understanding how familism values can confer protection for Latino youth in the face of risk (e.g., cultural protection or stress-buffering; Stein et al, 2014), such values have also been directly associated with well-being and better physical health (e.g., promotive factors; Corona, Campos, & Chen, 2017). For example, Schwartz et al (2010) found that prioritizing the family was highly correlated with self-esteem, life satisfaction, and overall well-being in a diverse sample of college students.…”
Section: Familism Values and Latino Adolescent Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…While most research has focused on understanding how familism values can confer protection for Latino youth in the face of risk (e.g., cultural protection or stress-buffering; Stein et al, 2014), such values have also been directly associated with well-being and better physical health (e.g., promotive factors; Corona, Campos, & Chen, 2017). For example, Schwartz et al (2010) found that prioritizing the family was highly correlated with self-esteem, life satisfaction, and overall well-being in a diverse sample of college students.…”
Section: Familism Values and Latino Adolescent Developmentmentioning
confidence: 99%
“…Beyond indices of socioemotional and mental health, emerging research has also identified that familism values may promote better physical health and use of physician care in samples of Latino adolescents and young adults (Corona, Campos, et al, 2017; Updegraff et al, 2017). However, very little research has examined the potential pathways through which familism values may be associated with both physical and mental health, particularly during adolescence.…”
Section: Familism Values and Latino Adolescent Developmentmentioning
confidence: 99%
“…F amilism, characterized by an emphasis on collective needs, interdependency, and conformity, along with a deeply ingrained sense of obligation and orientation to the family, has received increasing scholarly attention as it has been shown to serve as a protective factor for certain subpopulations of youth (see, e.g., Corona, Campos, & Chen, 2017;German, Gonzales, & Dumka, 2009). While familism is recognized as a hallmark of Hispanic culture (see, e.g., Schaefer, 2008, Schwartz, 2007Killoren et al, 2015), with several scales validated for various Latino populations (Lugo-Steidel & Contreras, 2003), familism's central role among other collectivist ethnic groups has also been noted (Schwartz, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In Hispanic and Latin-American cultures, familism is considered a crucial protective factor for physical and psychological well-being, especially during periods of crisis and psychological distress (Campos, Ullman, Aguilera, & Schetter, 2014;Valdivieso-Mora, Peet, Garnier-Villarreal, Salazar-Villanea, & Johnson, 2016). Familism is associated with frequency of self-care behavior, treatment adherence, better disease management, practice of physical exercise and academic performance (Corona, Campos, & Chen, 2017;Halgunseth et al, 2017;Perez & Cruess, 2014). In addition, familism was positively associated with mental health and general life satisfaction (Fuller-Iglesias & Antonucci, 2016;Marsiglia, Booth, Baldwin, & Ayers, 2013;Ojeda & Piña-Watson, 2013).…”
mentioning
confidence: 99%
“…However, other research examining the influence of familism on psychological well-being has produced inconsistent results. For instance, familism has been described as both a risk factor (Valdivieso-Mora et al, 2016) and a protective factor (Corona et al, 2017) for depression. Others have found that familism confers a motivation for providing care, acceptance of the caregiving role, and perception of positive caregiving experiences (Mendez-Luck et al, 2016).…”
mentioning
confidence: 99%